Enhanced lipoxygenase activity is involved in the stress response but not in the harmful lipid peroxidation and cell death of short-term cadmium-treated barley root tip - Liptáková, Ľubica (Journal of plant physiology, 2013)
Copyright © 2013 Elsevier GmbH. All rights reserved.